Cohesive theoretical framework in measuring teachers' innovative behavior in Malaysia - Johari, Aduni; Abdul Wahat, Nor Wahiza (Faculty of Educational Studies, Universiti Putra Malaysia, 2019)
On July 2019, Ministry of Education (MoE) has launched the PPPM 2013-2025 (Pelan Pembangunan Pendidikan Malaysia) 2018 Annual Report. It indicated that after six years of implementation, there was an improvement in five key areas in the Malaysian Education Development Plan. The five main aspects are access to education, improving quality in education, equity in education, developing student values and personality and strengthening unity through education as well as enhancing efficiency in Education. This is a good indicator in confirming the Malaysian’s school standard curriculum that stresses on the importance for innovations to be integrated in teaching and learning practices to ensure quality preparation of all students to life and work. Henceforth, the education system has been transformed to produce balanced, creative, critical and innovative people through communication, science and technology, physical and aesthetic development, self-esteem, humanity and spirituality as well as attitudes and values. It is important that the educators need to exhibit innovative behaviour to nurture the students in a smooth and systematic manner in accordance to the MoE philosophy. Under the National Philosophy, the education system is designed to produce citizens who are apart from being knowledgeable and competent, yet also able to contribute to the betterment of the nation at large. The innovative nature of education is determined by the teachers’ innovative behaviour and their ability to generate, create, develop, apply, promote, realize and modify new ideas to improve their teaching and students’ learning performance. Therefore, this conceptual paper is prepared to develop a theoretical framework for assessing the teachers’ innovative behaviour in several public schools in Malaysia. Among the major latent factors that have analytical potential of teacher’s innovative behaviour are perceived supervisory support, teamwork and humor. The theoretical foundation used for this study is the integration of Stage Model of Innovative Behavior, Bandura’s Social Cognitive Theory and Social Exchange Theory.